Methamphetamine abstinence induces changes in μ-opioid receptor, oxytocin and CRF systems: Association with an anxiogenic phenotype. (June 2016) - Georgiou, Polymnia; Zanos, Panos; Garcia-Carmona, Juan-Antonio; Hourani, Susanna; Kitchen, Ian; Laorden, Maria-Luisa; Bailey, Alexis
Abstract: The major challenge in treating methamphetamine addicts is the maintenance of a drug free-state since they experience negative emotional symptoms during abstinence, which may trigger relapse. The neuronal mechanisms underlying long-term withdrawal and relapse are currently not well-understood. There is evidence suggesting a role of the oxytocin (OTR), μ-opioid receptor (MOPr), dopamine D2 receptor (D2 R), corticotropin-releasing factor (CRF) systems and the hypothalamic-pituitary-adrenal (HPA)-axis in the different stages of methamphetamine addiction. In this study, we aimed to characterize the behavioral effects of methamphetamine withdrawal in mice and to assess the modulation of the OTR, MOPr, D2 R, CRF and HPA-axis following chronic methamphetamine administration and withdrawal. Ten-day methamphetamine administration (2 mg/kg) increased OTR binding in the amygdala, whilst 7 days of withdrawal induced an upregulation of this receptor in the lateral septum. Chronic methamphetamine treatment increased plasma OT levels that returned to control levels following withdrawal. In addition, methamphetamine administration and withdrawal increased striatal MOPr binding, as well as c-Fos + /CRF + neuronal expression in the amygdala, whereas an increase in plasma corticosterone levels was observed following METH administration, but not withdrawal. No differences were observed in the D2 R binding following METH administration and withdrawal. The alterations in the OTR, MOPr and CRF systems occurred concomitantly with the emergence of anxiety-related symptoms and the development of psychomotor sensitization during withdrawal. Collectively, our findings indicate that chronic methamphetamine use and abstinence can induce brain-region specific neuroadaptations of the OTR, MOPr and CRF systems, which may, at least, partly explain the withdrawal-related anxiogenic effects. Highlights: METH withdrawal induces anxiety-related symptoms in mice. METH administration and withdrawal causes neuroadaptations in the OT system. Persistent increase in striatal MOPr following METH treatment. Amygdalar c-Fos + /CRF + neurons are increased in METH-treated/withdrawn mice.